Journal Review: Potential of Orange Peel, Fruit, and Vegetable Waste as an Environmentally Friendly Electrolyte Source for Bio-Batteries - Suriana, I Wayan; Antari, Ida Ayu Dwi Giri; Ariastina , Wayan Gede; Setiawan, I Nyoman (Journal La Lifesci, 2025)
The ever-increasing demand for electrical energy demands alternative, environmentally friendly, and sustainable energy sources. Conventional batteries generally rely on synthetic chemicals that have the potential to pollute the environment. One solution that is beginning to be developed is the use of organic waste as an electrolyte source in bio-batteries. This review article discusses the potential of orange peel, fruit, and vegetable waste as a natural electrolyte containing organic acid compounds, particularly citric acid (C₆H₈O₇), as well as mineral acids that can decompose into ions in solution, thus conducting electricity. Various research results show that the acid and water content of organic waste can produce a potential difference when paired with dissimilar metal electrodes, thus generating an electric current. In addition, the pH characteristics and natural electrolyte content of the waste indicate its suitability as a substitute for hazardous chemicals in batteries. Thus, the use of orange peel, fruit, and vegetable waste has the potential to become an environmentally friendly bio-battery innovation that can support efforts to reduce dependence on conventional batteries while contributing to sustainable organic waste management.